How sustainability accounting can be a strategic tool in the Singapore hospitality sector. - Soo, Wei Chieh. (2010)
In an increasingly globalized world where monetary and operating capital flow across traditional borders of national definition, the ascendancy of companies warrants further thought on how they should conduct themselves as citizens just like any other person; political governance has its limits, and the welfare of the society with its environment is vested in the contemporary concept of corporate governance – companies must define the values they hold as citizens of a natural world.